2023
DOI: 10.1161/circulationaha.122.062486
|View full text |Cite
|
Sign up to set email alerts
|

Decongestion With Acetazolamide in Acute Decompensated Heart Failure Across the Spectrum of Left Ventricular Ejection Fraction: A Prespecified Analysis From the ADVOR Trial

Abstract: Background: Acetazolamide inhibits proximal tubular sodium reabsorption and improved decongestion in the Acetazolamide in Decompensated heart failure with Volume OveRload (ADVOR) trial. It remains unclear whether the decongestive effects of acetazolamide differ across the spectrum of left ventricular ejection fraction (LVEF). Methods: This is a pre-specified analysis of the randomized, double blind, placebo-controlled ADVOR trial that enrolled 519 patients with acute heart failure, clinical signs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Yet, assuming that the effect of SGLT2 inhibitor on volume homeostasis occur and are durable, it is difficult to know if treatmentmediated changes in the volume set point (if any) contribute to the effect of these drugs to reduce the risk of major heart failure events. Short-or long-term use of many conventional natriuretic and aquaretic drugs has not reduced cardiovascular death or hospitalizations for heart failure, 136,[138][139][140]157 demonstrating that immediate changes in urinary sodium or water excretion do not yield long-term clinical benefits. It is possible that the effects of SGLT2 inhibitors on sodium avidity may differ from other agents, but the volume effect of these drugs is small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, assuming that the effect of SGLT2 inhibitor on volume homeostasis occur and are durable, it is difficult to know if treatmentmediated changes in the volume set point (if any) contribute to the effect of these drugs to reduce the risk of major heart failure events. Short-or long-term use of many conventional natriuretic and aquaretic drugs has not reduced cardiovascular death or hospitalizations for heart failure, 136,[138][139][140]157 demonstrating that immediate changes in urinary sodium or water excretion do not yield long-term clinical benefits. It is possible that the effects of SGLT2 inhibitors on sodium avidity may differ from other agents, but the volume effect of these drugs is small.…”
Section: Discussionmentioning
confidence: 99%
“…Although intensive short-term diuresis to achieve hemoconcentration in hospitalized patients is associated with lower cardiac filling pressures, 153 early decongestion has not been associated with improved outcomes in observational studies or clinical trials. 138–141,154,155 More intensive treatment with intravenous loop diuretics yields a greater short-term diuresis, but does not reduce heart failure events at 60 days. 138 The addition of hydrochlorothiazide to a loop diuretic yields a modest diuretic effect, but no effect on death or rehospitalization at 90 days.…”
Section: Effect Of Sglt2 Inhibitors On Edema and Congestionmentioning
confidence: 99%
“…Posthoc analyses suggested that the observed decongestive effects of acetazolamide were chiefly mediated by its effect on natriuresis [36 & ]. Acetazolamide use increased the chance of successful decongestion across the entire spectrum of left ventricular ejection fraction [37]. Its use in the ADVOR trial prevented the development of loop diuretic induced metabolic alkalosis, which reflects neurohumoral activation and might play an important role in the occurrence of diuretic resistance [38].…”
Section: Acetazolamidementioning
confidence: 99%
“…9,10 In cases of HF with reduced nonvalvular ejection fraction, timely and effective treatment is essential, as failure to control the condition promptly may lead to complications that severely jeopardize the patients' life. 11 While medications for treating HF with reduced nonvalvular ejection fraction can provide temporary relief of clinical symptoms in patients, their long-term treatment outcomes are not always optimal, impacting patients' prognosis and overall quality of life. [12][13][14] Following HF education intervention, the treatment outcomes for HF patients showed significant improvement, aligning with findings from previous studies.…”
Section: Comparative Analysis Of the Incidence Of Adverse Cardiovascu...mentioning
confidence: 99%